Questioning the Architectural Envelope-Context Relationship in Contemporary Architecture - Duzgun, Hande; Polatoglu, Cigdem (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2016)
Every building is characterized by an architectural envelope-the interface between interior and exterior. The semantic significance of the envelope has been redefined by a changing understanding of context in the contemporary architectural environment. As the architectural agenda is continuously transformed, these approaches have been opened to multi-dimensional discussion of symbol, value, language, and expression. Discussions regarding the conceptual reading of an architectural envelope and its constituent elements as a new means of definitional expression will reveal the place of the new meaning, definition, and scope of the architectural envelope in the contemporary understanding of architecture. The aim of the present paper was to offer evidence that the architectural envelope is a very important part of a building, that, as a basic construction element, it defines the building by determining its identity, represents the dynamic tension between interior and exterior, and has semantic, technological, and aesthetic value. A secondary aim was to emphasize that interrelationships described as re-defining and re-explaining the context, context becomes concept, and concept/concepts become context may be relevant in a new scope of architecture. Changing conceptions of the architectural envelope-context in the current architectural environment is discursively analyzed. A new perspective on the envelope-context relationship has been presented in recent architectural discourses during which conceptual openings and diversity of codes have been proposed in an effort to promote new design.
Keywords: Context; contemporary architecture; concept; architectural envelope; discourse analysis; Architecture